Acid-resistant chemotactic DNA micromotors for probiotic delivery in inflammatory bowel disease - Zinan Zhao; Yao Xu; Yong Hu (Nature Communications)
Abstract Microcapsules composed of synthetic polymeric matrices have attracted considerable attention in delivering oral probiotics. However, existing polymeric microcapsules demonstrate inadequate acid resistance and adaptability, as well as deficiency in the inflamed colon-specificity and uncontrolled release of probiotics therein. Herein, a DNA microcapsule is prepared as a probiotic-transporting micromotor through photo-crosslinking of hyaluronic acid methacrylate and acrydite-modified A-/C-rich oligomers within the microfludically generated droplets in the presence of nitric oxide-cleavable crosslinker and gas donor manganese carbonyl (MnCO). As the microcapsules traverse stomach, duodenum, and ultimately colon, the formation and dissociation of A-motif and i-motif structures instigate a reversible shrinking-swelling transition of microcapsules to preserve probiotic viability. Subsequently, the microcapsules exhibit chemotaxis towards inflamed colon site, driven by a gas-generating reaction between MnCO and elevated reactive oxygen species. Following disintegration of the microcapsules, triggered by endogenous nitric oxide, probiotics are released to reshape the dysbiosis of intestinal microflora. This advanced delivery system offers significant promise for the effective clinical management of inflammatory bowel disease.